Preliminary validation for an online configuration determination method of a thin film buckling under point contact force - Yeoun-Jae Kim; Daehan Wi (Scientific Reports)
Abstract The authors previously developed an online thin film buckling configuration determination method for a mini basket type mapping catheter prototype, which incorporates eight thin film sensor strips. In the prior study, no external force was applied to the thin film, and only axial displacement was adjusted to induce buckling in the thin film. Extending this prior work, a preliminary methodological validation is conducted for an online configuration determination method of thin film buckling under a point contact force. The overall thin film configuration determination problem is formulated as a constrained optimization problem, involving five variables and five equality constraint functions. Before developing an actual online optimization solver, preliminary numerical calculations, Ansys simulations, and experiments are performed to verify the proposed problem formulation. The comparison between the numerical precalculations, Ansys simulations, and experimental results demonstrated that the proposed problem formulation is consistent with Ansys simulations and experimental outcomes. This indicates that the proposed formulation is capable of calculating accurate solutions using appropriate optimization methodologies.